Nonuniform 2D microstrip antenna arrays for wireless applications - Varum, Tiago Miguel Valente (2016)
Wireless communications have undergone over the last decades a tremendous progress as a consequence of the exponential growth in demand for mobile devices, and nowadays are more and more involved in people's lives. This presence is re ected through the use of a large number of applications of which they become increasingly dependent on. The antenna, in its most di erent forms, are crucial elements in the establishment this type of communication. Each application involves a number of speci c characteristics, whereby, the improvement of wireless communications is related to the appropriateness of the used antenna. Many applications require antennas with radiation pattern with its particular shapes (in terms of beamwidth, side lobes levels, direction, etc ..), static or dynamic (adaptive antennas), involving in most cases the use antenna arrays to meet to such constraints. In this thesis, a number of techniques to synthesize antennas consisting of planar arrays with nonuniform excitation of their elements, are addressed. A group of the direction of arrival and beamforming estimation algorithms are also presented and analyzed, in order to enable their application in adaptive antenna array with dynamic beamforming. A vast and diversi ed set of arrays with di erent radiation requirements, and for di erent applications were developed. These arrays have great applicability in current research topics in antennas, such as vehicle communications, Wi-Fi in sports venues and smart antennas.